On the sociology of cartels - Justus Haucap; Christina Heldman (European Journal of Law and Economics, 2023)
We analyze 15 German cartels, focusing on the personal characteristics of the individual participants, the methods and frequency of communication as well as the internal organizational structures within the cartels and their eventual breakup. Our results indicate that cartel members are highly homogeneous and often rely on existing networks within the industry, such as trade associations. Most impressively, only two of the 158 individuals involved in these 15 cartels were female, suggesting that gender plays a role for cartel formation. We further identify various forms of communication and divisions of responsibilities and show that leniency programs are a powerful tool in breaking up cartels. Based on these results we discuss implications for competition policy and further research.
Keywords: L41; K42; D43; 340; Cartels; Collusion; Social networks; Trust; Antitrust